Pediatric Patients with Osteomyelitis and/or Septic Joint Undergoing Surgical Debridement Have Equivalent Short-Term Outcomes with or without Preoperative MRI - E. Graham Englert; Collin L. Braithwaite; Maria E. Aguirre-Flores; Aaron W. Lam; Mohamed Sarraj; Abigail Kumagai; E. Dimitra Bednar; Adam M. Gordon; Ibrahim Salama; Jacob Keeley; Indu Pathak; Waleed Kishta; et al. (MDPI AG, 2024)
The purpose of this study was to determine if short-term outcomes differed for pediatric patients with suspected musculoskeletal infection with or without a preoperative MRI. This was a multicenter, retrospective review of patients aged 0-16 years who presented with atraumatic extremity pain, underwent irrigation and debridement (I&D), and received at least one preoperative or postoperative MRI over a 10-year period. Primary outcomes were time to OR, total I&Ds, readmission rate, time from OR to discharge, and total number of MRIs. Secondary outcomes entailed the rate at which concurrent osteomyelitis was identified in patients with septic arthritis and the extent of the resulting surgical debridement. Of the 104 patients, 72.1% had a preoperative MRI. Patients with a preoperative MRI were significantly less likely to have surgery on the day of admission. No difference was found between groups regarding total I&Ds, readmission rate, time from OR to discharge, and total number of MRIs. Of the 57 patients diagnosed with septic arthritis, those with a preoperative MRI were significantly more likely to have concurrent osteomyelitis identified and to undergo bony debridement in addition to arthrotomy of the joint. In conclusion, patient outcomes are not adversely affected by obtaining a preoperative MRI despite the delay in time to OR. Although preoperative MRI can be beneficial in ruling out other pathologies and identifying the extent of concurrent osteomyelitis, the decision to obtain a preoperative MRI and timing of surgery should be left to the discretion of the treating surgeon.